'Not birth, marriage or death, but gastrulation': the life of a quotation in biology. Issue 1 (March 2022) - Hopwood, Nick
Abstract: This history of a statement attributed to the developmental biologist Lewis Wolpert exemplifies the making and uses of quotations in recent science. Wolpert's dictum, 'It is not birth, marriage or death, but gastrulation which is truly the most important time in your life', was produced in a series of international shifts of medium and scale. It originated in his vivid declaration in conversation with a non-specialist at a workshop dinner, gained its canonical form in a colleague's monograph, and was amplified as a quotation on a poster derived from an undergraduate project. Although it drew on Wolpert's authority and he accepted his authorship, it thus represents a collective sifting of earlier claims for the significance of prenatal existence through the values of 1980s developmental biology. Juxtaposing a technical term with major life events has let teachers engage students, and researchers entice journalists, while sharing an in-joke that came to mark community identity. Serious applications include arguing for an extension of the fourteen-day limit on human-embryo research. On this evidence, quotations have been kept busy addressing every audience of specialized knowledge.